Digital Competences and Years of Access to Technologies Among Chilean University Students: An Analysis Based on the Digcomp Framework - Silva-Quiroz, J (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
This study investigates the relationship between access time to digital technologies and the devel-opment of digital competences among Chilean university students, using the DIGCOMP-PED in-strument based on the DIGCOMP framework. Methods: The instrument was applied to 4360 first-year students at a Chilean public university, and an expert validation process was carried out to identify relevant competences for academic training. Results: The findings indicate a positive but non-linear relationship between years of experience using technologies and performance in certain areas of the DIGCOMP framework. Although the study was conducted between 2021 and 2022, with the follow-up analysis completed in 2024, access alone does not guarantee the acquisition of ad-vanced skills across all competences. Conclusions: The study emphasizes the complexity of the re-lationship between access to technology and the development of digital competences, highlighting the importance of pairing access with quality education and structured guidance in digital literacy to prepare students for the challenges of the digital world. © 2024 by the authors.